SYNTHESIS, CRYSTAL STUDIES AND PHARMACOLOGICAL ROLE PREDICTION OF 3-IODO-2- METHYL-1 PHENYL SULFONYL-1H INDOLE - CHINNATHAMBI, RAMATHILAGAM; SANTHANAM, VIJAYASRI; VADIVELU, MANIVANNAN; RAMACHANDRAN, UMARANI PADAGACHERI; Hopper, Waheeta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Indole-based compounds have established many pharmacological applications. Indole acts as a starting compound for various medicinal preparations. Our objective is to determine the possible pharmacological roles of our crystallized indole-based ligand using computational approach. The activities studied are antibacterial, antitubercular, and antimelanoma. Methods: The structure of the indole compound, CR2 was studied using single crystal X-ray diffraction technique. To predict the pharmacological activities, the structure-based docking method was followed. The protein targets were selected based on their important biological role in each activity mentioned above. The interactions between the targets and the crystal ligand were studied using a generic based docking algorithm. The significant pharmacophore features of the ligand were also reported. Results: The ligand showed bonded and non-bonded interactions with the crucial amino acid residues of the active site of each target. The interactions and the binding energies were quite comparable to the targets’ natural ligands. Conclusion: We suggest through the computational approaches that the ligand may have antitubercular, antibacterial, and antimelanoma activities with respect to the targets considered. The new insights of this compound as predicted by the computational methods are believed to provide a platform for the futuristic pharmacological activities of this compound that can be further considered for wet lab techniques. Keywords: Indole, Dihydrofolate reductase, DNA gyrase, Human B-Raf kinase, Docking, Pharmacophore, Single crystal X-ray diffraction.